(untitled) (Research, Society and Development, 2024)
Objective: To analyze the relationship between religious and/or spiritual beliefs and the quality of life of individuals undergoing dialysis, evaluate their adaptation to treatment, and explore the connection between spirituality, religiosity, and quality of life. Methodology: This is a Systematic Literature Review (SLR) using the PICO methodology to examine the relationship between religious and spiritual beliefs and quality of life in individuals with chronic kidney disease (CKD) undergoing dialysis. Studies published between 2014 and 2023 in Portuguese, English, and Spanish were selected from the B-On and PubMed databases. Seven studies were identified, exploring various dimensions of this relationship through qualitative and quantitative approaches. Results and Discussion: The studies indicate that spirituality and religiosity play significant roles in coping with CKD and improving the quality of life of individuals with the condition. A positive correlation between spirituality and hope is also highlighted, emphasizing the importance of faith in adapting to treatment and finding meaning in life. The cultural diversity of the selected studies reveals nuances in spiritual practices, influencing the global understanding and applicability of the results. Conclusions: The findings suggest that spirituality/religiosity can strengthen emotional resilience, improve the well-being of individuals with CKD, reduce depression, and provide emotional support. Understanding cultural differences and ensuring sensitivity in adapting spiritual interventions are crucial for offering more effective and appropriate care, respecting various religious and spiritual practices, as well as the absence of them.